2018
DOI: 10.1177/2192568218776653
|View full text |Cite
|
Sign up to set email alerts
|

Matched Cohort Analysis of Elective Lumbar Spinal Fusion in Patients With and Without Parkinson’s Disease: In-hospital Complications, Length of Stay, and Hospital Charges

Abstract: Study Design: Retrospective cohort. Objectives: Parkinson's disease (PD) is a neurodegenerative condition associated with significant morbidity and mortality. PD patients often develop spinal conditions and are known to have high complication rates following surgery. This study evaluated the outcomes of lumbar fusion surgery in patients with PD using a large, public, national database. Methods:The Healthcare Cost and Utilization Project (HCUP) Nationwide Inpatient Sample (NIS) was used to identify elective lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Life expectancy for patients with PD continues to increase due to improved care, which has resulted in a greater number of patients undergoing elective surgery 3. Postural instability, dystonia, bradykinesia, and the increased fall risk associated with PD present unique challenges to spine surgeons 4–8…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Life expectancy for patients with PD continues to increase due to improved care, which has resulted in a greater number of patients undergoing elective surgery 3. Postural instability, dystonia, bradykinesia, and the increased fall risk associated with PD present unique challenges to spine surgeons 4–8…”
mentioning
confidence: 99%
“…3 Postural instability, dystonia, bradykinesia, and the increased fall risk associated with PD present unique challenges to spine surgeons. [4][5][6][7][8] Previous studies report conflicting evidence regarding the effectiveness of elective lumbar surgery in patients with PD, with multiple studies reporting higher rates of complications and implant failure in those with PD. [9][10][11] While many studies have cautioned routine elective surgical treatment for lumbar pathology in patients with PD, several studies have reported similar complication rates between patients with and without PD, as well as significant improvement in patient-reported outcomes (PROs).…”
mentioning
confidence: 99%
See 2 more Smart Citations